A focus group study to seek the opinions of Malaysian geriatricians, pharmacists, and nurses about education materials on fall-risk-increasing drugs - Mohammad Suhaidi Shaari, Mohd Shahezwan Abd Wahab,, Rosmaliah Alias, Izzati Abdul Halim Zaki, Ali Omar Yassen, Hasnah Ismail (Journal of Applied Pharmaceutical Science, 2022)
Falls and related injuries are major public health problems among older people (OP). The use of fall-risk-increasing drugs (FRIDs) has been identified as a risk factor for falls, yet the use of the drugs among OP is common. Previous studies showed that OP have low awareness about FRIDs. Education materials (EMs) have the potential to be used to enhance knowledge of OP on various health-related topics including FRIDs. This study employed a focus group discussion (FGD) to seek the opinions of key stakeholders in OP care about EMs on FRIDs. Nineteen healthcare providers (HCPs) participated in the FGDs which were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. The HCPs believed that the awareness of OP about medications as a risk factor for falls is low. EMs on FRIDs were well received by the HCPs, and were associated with several benefits. Several topics were recommended to be included in the EMs with the aim to enhance the awareness and risk perceptions about FRIDs among OP and to promote HCP–patient communication about the drugs. The HCPs’ opinions may assist the development of EMs on FRIDs by informing the priorities and scope of content, thus ensuring the suitability and relevance for OP.
Keywords: Education material, fall-risk increasing drug, falls, older people, patient education